Efektifitas pemberian makanan tambahan (PMT) berbahan lokal terhadap berat badan dan status gizi balita: Tinjauan literatur - Mukodri, Dewi Mey Lestanti; Aminin, Fidyah; Safitri, Tiyara; Damayanti, Melly; Saputri, Nurul Aini Suria; Jasda, Asmarita; Ikhwan, Zainul; Jannah, Rawdatul; Putri, Sabtini Ika; Cintiani, Jeni Cesi (Poltekkes Kemenkes Aceh, 2025)
Background: Nutritional problems among toddlers remain a public health challenge in many regions, including Indonesia. Locally-based Supplementary Feeding (PMT) is often utilized to address nutritional issues, particularly in improving toddler weight and nutritional status.Objectives: This article aims to evaluate the effectiveness of locally-based supplementary feeding in improving toddler weight and nutritional status through a literature review.Methods: This literature review applied a narrative review approach by searching articles in PubMed and Google Scholar (2015–2024). Articles were selected based on inclusion criteria, including RCTs and observational studies discussing the impact of local PMT on toddler weight and nutritional status. Study quality was assessed using the Newcastle-Ottawa Scale and GRADE. Data were analyzed descriptively without quantitative meta-analysis.Results: Most studies reported that local PMT effectively increased toddler weight. However, its impact on nutritional status was often insignificant within a short intervention duration. Key factors determining the success of the intervention included nutrient composition, intervention duration, and adherence level.Conclusion: Local food-based PMT is effective in improving toddler weight, although it may not significantly change nutritional status in the short term. This intervention can serve as a relevant alternative to support toddler nutrition, especially in areas with limited access to nutritious food.